2015
DOI: 10.2135/cropsci2014.09.0637
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis for Triazine Herbicide Tolerance in Bermudagrass, Seashore Paspalum, and Zoysiagrass

Abstract: Atrazine and simazine control weeds in warm‐season turfgrasses, but excessive injury limits applications to sensitive species. The objective of this research was to evaluate the physiological basis for differential tolerances of bermudagrass (Cynodon dactylon (L.) Pers.), seashore paspalum (Paspalum vaginatum Sw.), and zoysiagrass (Zoysia japonica Steud.) to atrazine and simazine. In greenhouse experiments, hierarchical shoot mass reductions from the nontreated by species were: seashore paspalum > bermudagrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…Absorption was similar across harvests suggesting radioactivity was not lost after returning plants to the hydroponic tank at 24 HAT. Reduced absorption of DR3 agrees with findings of Singh et al (2015) showing increased metabolism coupled with reduced absorption results in higher simazine tolerance for zoysiagrass (Zoysia japonica Steud.) and bermudagrass when compared with the more sensitive seashore paspalum (Paspalum vaginatum Sw.).…”
Section: Resultssupporting
confidence: 88%
“…Absorption was similar across harvests suggesting radioactivity was not lost after returning plants to the hydroponic tank at 24 HAT. Reduced absorption of DR3 agrees with findings of Singh et al (2015) showing increased metabolism coupled with reduced absorption results in higher simazine tolerance for zoysiagrass (Zoysia japonica Steud.) and bermudagrass when compared with the more sensitive seashore paspalum (Paspalum vaginatum Sw.).…”
Section: Resultssupporting
confidence: 88%
“…The susceptibility of turfgrasses to herbicide injury has also been correlated with levels of root absorption. Singh et al (2015) reported seashore paspalum had greater root uptake of 14 C‐atrazine and 14 C‐simazine than turfgrasses with greater tolerance levels, bermudagrass and zoysiagrass ( Zoysia japonica L.). Yu et al (2013) reported annual bluegrass ( Poa annua L.) had greater root absorption of 14 C‐amicarbazone than creeping bentgrass ( Agrostis stolonifera L.) and tall fescue ( Festuca arundinacea Shreb.).…”
Section: Resultsmentioning
confidence: 97%
“…Reduced levels of root absorption have been attributed to annual bluegrass resistance to atrazine in the absence of a mutated D1 protein (Svyantek et al 2016). Root absorption levels also contribute to the selectivity of herbicides used for annual bluegrass control and the susceptibility of turfgrass species to injury from applications (Lycan and Hart 2006; McCullough et al 2016; Singh et al 2015; Yu and McCullough 2016; Yu et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Plant counts for the nontreated averaged 9 (±1.7 SE) and 6 (±1.5 SE) per pot for the R and S biotypes in Experiment 3, respectively, and 15 (±1.5 SE) and 25 (±2.7 SE) in Experiment 4, respectively. turfgrass species to injury from applications (Lycan and Hart 2006;McCullough et al 2016;Singh et al 2015;Yu and McCullough 2016;Yu et al 2013).…”
Section: Control a Experiments Herbicidementioning
confidence: 99%